2003
DOI: 10.1097/00129689-200306000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Approaches to the Management of Pancreatic Pseudocysts

Abstract: Although one third or more of pancreatic pseudocysts might resolve spontaneously, interventional therapy is required for most. Several minimally invasive management approaches are now available, including percutaneous drainage under radiologic control, endoscopic transpapillary or transmural drainage, and laparoscopic internal drainage. This paper reviews the methodology, applications, advantages, shortcomings, and results of these management approaches. A computerized search was made of the MEDLINE, PREMEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 78 publications
2
64
0
Order By: Relevance
“…Percutaneous drainage in the case of pancreatic cysts is in 67-90% of cases the final method of treatment, which was confirmed in our study (89.5%) (1,5,6,7,(10)(11)(12)(13)(14). It should be noted that the basis for drainage removal (when the release is below 10ml/day) is the completion of fistulography via the drain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Percutaneous drainage in the case of pancreatic cysts is in 67-90% of cases the final method of treatment, which was confirmed in our study (89.5%) (1,5,6,7,(10)(11)(12)(13)(14). It should be noted that the basis for drainage removal (when the release is below 10ml/day) is the completion of fistulography via the drain.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, despite the tremendous differences in the clinical courses of these two conditions, treatment by means of percutaneous drainage is considered together for these two complications. Since endoscopic ultrasound (EUS) permits imaging local anatomical relations, it introduced new possibilities for performing endoscopic drainage of post-inflammatory pancreatic liquid cisterns (5,9).…”
Section: Discussionmentioning
confidence: 99%
“…External drainage is a simple method and mainly applied in emergency cases of secondary infection, rupture, or hemorrhage, but it is reported that recurrence is more likely to occur with high rate of infection and pancreatic fistula. 3,4 Endoscopic internal drainage is an alternative; however, the effect of drainage is not always satisfactory due to the inadequate communication created, and hemorrhage and perforation often happen. All these disadvantages of endoscopic drainage lead to a high rate of failure and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various laparoscopic techniques have been described [8,9,10,11,12,13]. Our indication for this procedure is that the pseudocyst is >6 cm and has persisted beyond 6 weeks [14,15,16,17]. Three patients were treated conservatively with pseudocysts <6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The median size of pancreatic pseudocysts was 16.6 cm (range 12–19). Our indication for this procedure is that the pseudocyst is >6 cm and has persisted beyond 6 weeks [14,15,16,17]. …”
Section: Methodsmentioning
confidence: 99%